2018
DOI: 10.1111/ele.12956
|View full text |Cite
|
Sign up to set email alerts
|

Calcium plus magnesium indicates digestibility: the significance of the second major axis of plant chemical variation for ecological processes

Abstract: Plant variation in nutrient concentrations encompasses two major axes. The first is connected to nitrogen (N) and phosphorus (P), reflects growth rate and has been designated as the leaf economics spectrum (LES) while the second follows the gradient in calcium (Ca) and magnesium (Mg) and mirrors cell structural differences. Here, we tested in grasslands whether the sum Ca + Mg concentrations is a better indicator of digestibility than LES constituents. Structural equation modelling revealed that the total effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 60 publications
(87 reference statements)
5
33
0
Order By: Relevance
“…Interestingly, in our experiment, we found that nutrient contents (N and Ca) were about twice as important as structural components (LDMC and fibres) in determining litter quality (combined path coefficients of 0.61 for nutrients and -0.36 for structure). Effects of N have been shown in many studies (Garnier et al, 2004;Cornwell et al, 2008) and as pointed out in Mládková, Mládek, Hejduk, Hejcman, and Pakeman (2018), Ca and Mg content (which were highly correlated in our case) also indicate a better digestibility and a higher decomposability of the litter (García-Palacios et al, 2016a). Ca and Mg are key components of invertebrate diets and can therefore increase their abundance (National Research Council, 2005), which may explain their positive effects on decomposition.…”
Section: Functional Composition Is the Main Driver Of Litter Qualitysupporting
confidence: 77%
“…Interestingly, in our experiment, we found that nutrient contents (N and Ca) were about twice as important as structural components (LDMC and fibres) in determining litter quality (combined path coefficients of 0.61 for nutrients and -0.36 for structure). Effects of N have been shown in many studies (Garnier et al, 2004;Cornwell et al, 2008) and as pointed out in Mládková, Mládek, Hejduk, Hejcman, and Pakeman (2018), Ca and Mg content (which were highly correlated in our case) also indicate a better digestibility and a higher decomposability of the litter (García-Palacios et al, 2016a). Ca and Mg are key components of invertebrate diets and can therefore increase their abundance (National Research Council, 2005), which may explain their positive effects on decomposition.…”
Section: Functional Composition Is the Main Driver Of Litter Qualitysupporting
confidence: 77%
“…Considering the known link of these traits with the decomposable litter fraction, the strong effect of invader-induced changes in these traits on litter decomposition in our study, is thus hardly surprising (Makkonen et al, 2012;Mládková et al, 2018). Previous research in our study system has furthermore indicated that the shifts in the community trait composition are largely effectuated through intraspecific trait changes induced by competition with the invader, rather than through species composition changes (Helsen, Van Cleemput, Bassi, Graae, et al, 2020).…”
Section: Invader Impact On Litter Decompositionsupporting
confidence: 44%
“…Plant height (cm) and leaf area (mm 2 ) are proxies for the second axis of the global spectrum of plant form and function ('size of whole plants and their parts'), which relates to competitive ability (Díaz et al, 2016). Leaf mass per area (LMA, g/cm 2 ), leaf dry matter content (LDMC, mg/g) and leaf nitrogen (N), phosphorous (P) and potassium content (K; mg/mm 2 ) are related to the leaf economics spectrum (Cornelissen & Thompson, 1997;Cornwell et al, 2008) and leaf magnesium (Mg) and calcium content (Ca; mg/ mm 2 ) relate more directly to labile litter fraction components, such as pectin and chlorophyll units (Makkonen et al, 2012;Mládková et al, 2018). Note that all leaf nutrients were expressed on area basis, rather than mass basis to enhance comparability with the retrieved optical traits.…”
Section: Functional Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it was interesting to see the potential importance of Ca and Mg in explaining the variation in nutrient dynamics in both fine root and twigs. This reflects the important role of these elements in decomposition [35,36].…”
Section: Initial Chemistry and Nutrients Dynamics During Decompositionmentioning
confidence: 83%